Teaching Entrepreneurial Mindset: Lessons from Dead Poets Society - Neck, Heidi M.; W. Gerde, Virginia (Senate Hall, 2007)
Film captures the complexity of issues, of possibilities and of interactions among diverse people. It can be very effective in the classroom because it draws students into the situation and provides them with an engaging opportunity to grapple with concepts and theories. Building off of the work of van Gelderen and Verduyn (2003), we describe how Dead Poets Society, a non-business film, can be used with entrepreneurship students to facilitate a discussion on entrepreneurial thinking and behavior - the entrepreneurial mindset. We highlight eight lessons for entrepreneurs that emerge from viewing a series of film clips. Alternative pedagogical uses for the film are also discussed.
Keywords: pedagogy|film|movie|entrepreneurial mindset|entrepreneurial behavior